REBUILDING THE PROFESSIONAL TEACHING CAPACITY OF UNDERGRADUATE ENGLISH EDUCATION STUDENTS OF UIN ALAUDDIN MAKASSAR (A Case Study on Student-Teachers of PBI Students of Tarbiyah Faculty) - Mardiana Nurdin (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2014)
Abstrak: Penelitian ini bertujuan untuk mengeksplorasi kapasitas pengajaran yang profesional mahasiswa PPL PBI UIN Alauddin Makassar yang melibatkan 4 guru pamong dan 30 mahasiswa PPL. Data dikumpulkan melalui survei online, lembar pengamatan dan dokumentasi yang dianalisis dengan menggunakan metode campuran qualitatif dan kuantitatif. Penelitian ini menyimpulkan bahwa: 1) mahasiswa PPL berpendapat bahwa seorang guru bahasa Inggris seharusnya mampu melakukan tanggung jawabnya sebagai seorang guru yang memiliki kompetensi paedagogik, profesional, sosial, dan kepribadian, 2) mahasiswa PPL cenderung menerima pebelajar mandiri, kerja berpasangan dan kerja kelompok, mengadaptasi pengajaran untuk memenuhi kebutuhan siswa sebelum praktik pembelajaran, tetapi cenderung menguranginya selama proses pembelajaran; mahasiswa PPL juga cenderung menerima pengajaran grammar secara eksplisit, koreksi kesalahan, dan pengucapan seperti penutur asli, pengetahuan teknikal, dan keterampilan interpersonal sebelum praktik mengajar dan meningkatkan proporsinya selama proses mengajar, 3) Guru pamong berpendapat bahwa mahasiswa PPL PBI UIN alauddin harus meningkatkan kemampuan bahasa Inggris, penggunaan metode pengajaran yang inovatif, penilaian autentik, dan penggunaan media yang bervariasi.Abstract: This research aims to explore the professional teaching capacity of undergraduate English education students of UIN Alauddin Makassar. It involves 4 supervising-teachers and 30 student-teachers. The data were collected through online survey questionnaires, feedback observation sheets and documentation; analyzed quantitatively and qualitatively. The research finds that: 1) the student-teachers perceive an EFL teacher should be able to do their responsibilities which involves pedagogic, professional, social, and personal competences; 2) the student-teachers have a tendency to accept learner autonomy, pair/group work, adapting teaching to cater for learner needs before the teaching-practice but tend to decrease some parts of it during the teaching-practice; the student-teachers are likely to accept explicit grammar instruction, error correction and native like pronunciation, technical knowledge and interpersonal skills before the teaching-practice and increase the proportion of them during the teaching-practice; 3) The supervising-teachers considered that the student-teachers of PBI UIN Alauddin Makassar still need to improve their English speaking ability, the use of innovative EFL teaching methods and authentic assessment and the use of different kind of teaching media.